Long-Lasting Insecticide-Incorporated Netting and Interception Traps at Pilot-Scale Warehouses and Commercial Facilities Prevents Infestation by Stored Product Beetles - Wilkins, Rachel V.; Campbell, James F.; Zhu, Kun Yan; Starkus, Laura A.; McKay, Tanja; Morrison, William R. (Frontiers in Sustainable Food Systems, 2021)
At any point along the post-harvest supply chain, commodities are vulnerable to insect infestation. This is due to a variety of factors, but includes landscape-scale movement of stored product insects to and from food facilities and natural refugia. Long-lasting insecticide-incorporated netting (LLIN) is an innovative tactic that may be used to intercept immigrating insects. LLIN can be used to cover gaps in architecture (e.g., vents, windows, eaves, or over pallets of goods) at food facilities. Another novel approach would be to use LLIN as a kill mechanism in attract-and-kill inspired interception traps on the perimeter of facilities. Furthermore, employing these two LLIN-based approaches together would create multiple protective barriers to reduce infestation in commodities. Therefore, the goal of the current study was to (1) examine the ability of interception traps to capture stored product insects at commercial wheat and rice food facilities, (2) assess whether LLIN deployment method affected efficacy in preventing infestation by stored product insects in pilot-scale warehouses, and (3) determine the success of using LLIN alone, interception traps alone, or both together to prevent infestations. Over 2 years, interception traps deployed for 48-h periods on the perimeter of commercial food facilities captured over 3,000 insects, representing 14 stored product insect taxa. Warehouses deploying LLIN exhibited an 89–93% and 98–100% reduction in insects reaching and progeny production in commodities, even after the release of 3,600 insects of three species over 12 weeks. The combined use of LLIN and interception traps did not improve control above LLIN alone, but this may be because insects could fly unencumbered, highlighting the importance of covering gaps with LLIN on food facilities.